Penerapan Metode EOQ dan ROP (Studi Kasus: PD. BARU) - Tomi Lukmana; Diana Trivena Yulianti (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
Abstract â€”PD.Baru not using technology that can manage system in computerized, still keep data records in manual. So the risk is very easy to lose the data transaction and requires the calculation of the optimal measuring instrument purchase the following year and to know the point of safe supply stock to make a reservation back. Therefore, created a desktop application that has the features to manage sales, purchasing and inventory by using Economic Order Quantity and Re Order Point. Applications created using programming languages C# and using database SQL Server 2008. This application testing system using the method black box, by using the method black box this may indicate that the application has been able to meet the expected result. Expected after PD.Baru to implement this application, PD.Baru can manage well.Â Keywords: sales, purchasing, eoq, rop, desktop.